2021
DOI: 10.3390/diagnostics11020172
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TEG Analysis in Patients with COVID-19-Associated Coagulopathy: A Systematic Review

Abstract: Coronavirus disease 2019 (COVID-19)-associated coagulopathy (CAC), characterized by hypercoagulability and an increased risk of thrombotic complications, is an important consideration in the management of patients with COVID-19. As COVID-19 is a new disease, no standard of care for the diagnosis or management of its associated coagulopathy is yet established. Whole blood viscoelastic tests, such as thromboelastography (TEG® hemostasis analyzer), analyze whole blood to provide a complete overview of the coagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 48 publications
5
86
1
Order By: Relevance
“…Conclusions of the previously published reviews are summarized in Table 11. Overall, the four reviews reported the same findings as we do: COVID-19 patients displayed an abnormal VET pattern [69][70][71][72], but further studies are needed for various reasons. Moreover, we challenge the idea that such a pattern represents hypercoagulability; one main reason is that inhibitory systems are not at all taken into account, in sharp contrast with TGAs.…”
Section: Summary Of the Conclusion Of The Previously Published Reviewssupporting
confidence: 75%
See 4 more Smart Citations
“…Conclusions of the previously published reviews are summarized in Table 11. Overall, the four reviews reported the same findings as we do: COVID-19 patients displayed an abnormal VET pattern [69][70][71][72], but further studies are needed for various reasons. Moreover, we challenge the idea that such a pattern represents hypercoagulability; one main reason is that inhibitory systems are not at all taken into account, in sharp contrast with TGAs.…”
Section: Summary Of the Conclusion Of The Previously Published Reviewssupporting
confidence: 75%
“…There are numerous methodological differences among the 44 studies using VETs to assess the hemostasis in COVID-19 patients we have retrieved and analyzed, explaining why results were not consistent through studies, or sometimes even conflicting. This was already raised by previously published reviews [70,71].…”
Section: Methodological Issues In Vet Studiesmentioning
confidence: 82%
See 3 more Smart Citations